Delusional Infestation - Laupland, Kevin B. (Can J Infect Dis Med Microbiol, 2016)
Although the practice of infectious diseases involves a broad range of surgical and medical disciplines, interactions with psychiatry are infrequent. Delusional infestation is a condition where an individual has a firmly fixed false belief that they have an infection. Delusional infestation challenges the infectious diseases specialist who must diligently rule out the presence of a true infection. However, perhaps, more importantly, we may need to initiate therapy with neuroleptic medications for which we may have little specific knowledge and experience. In this note we review the diagnosis and management of patients with delusional infestation.